Bone autografts & allografts placed simultaneously with dental implants in rabbits. Issue 1 (January 2018) - Ribeiro, Marna; Fraguas, Erica Hohlenwerger; Brito, Keila Ilse Cangussu; Kim, Yeon Jung; Pallos, Debora; Sendyk, Wilson Roberto
Abstract: Objective: This study compared stability, removal torque, bone implant contact (BIC) and area (BA) of implants installed simultaneously with onlay autografts or allografts in rabbits' tibias. Material and methods: Total of 18 rabbits were used in this study. Fresh frozen allografts were obtained from six animals at T(-6). Two implants with autogenous grafts (Group 1) or allografts (Group 2) were simultaneously inserted into both sides of the tibiae in a vertical periimplant defect model at T0. The resonance frequency (ISQ) was measured in implant proximal epiphysis on the day of installation of T0 and T18 (18 weeks post-surgery). At T18 the removal torque was assessed at the distal implants, the implants' proximal epiphysis and surrounding bone were harvested to perform histomorphometric analysis. The BIC and BA within the limits of the implants threads were evaluated. Results: The ISQ revealed a statistically significant difference between T0 and T18 in each group (p = 0.024, p = 0.003). The removal torque indicates that there was no significant difference between the two groups (p = 0.47). No significant differences were observed between the groups regarding both BIC (p = 0.3713) and the BA (p = 0.3883). Conclusion: Both grafts and implants demonstrated the same stability, torque removal and the BIC and BA.